HUBUNGAN ANTARA PENERAPAN PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT (STBM) DENGAN KEJADIAN DIARE DI WILAYAH KERJA PUSKESMAS SALO KABUPATEN KAMPAR TAHUN 2017 - Novita Rany (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2019)
The occurrence of diarrhea is still high and the top 10 diseases in the work area of the salo clinic, in line with poor sanitary conditions, especially open bowel behavior which reaches 35% of the population. The purpose of this study was to determine the relationship between the implementation of STBM program with the occurrence of diarrhea in Salo Puskesmas Kampar District. This research is an observational analytic research with cross sectional approach. The population of this study were all households living in Salo Community Health Center. The sample is 36 households. The sampling technique used proportional random sampling. Data analysis using chi square test. The measuring instruments used were questionnaires and observations. The result of the research shows that there is correlation between indiscriminate defecation (p value = 0,001), CTPS (p value = 0,010), Water and Household Food Management (P value = 0,040), household waste management (p value = 0,004), Household Liquid Waste (p value = 0.001) with the incidence of diarrhea in Salo Community Health Center. It is expected that the Village and the Community Health Center will provide information to the public through health promotion activities on the five pillars of STBM.